Free Pasture of Exotic Goats Reduces Diversity and Negatively Affects Body Condition in Scorpions (Arachnida: Scorpiones) Assemblage From Brazilian Seasonal Dry Tropical Forest - Thayna Rhayane Brito‐Almeida; Stênio Ítalo Araújo Foerster; José Rivaldo Lima; Meykson Alexandre daSilva; Geraldo Jorge Barbosa deMoura; André Felipe deAraujo Lira (Ecology and Evolution)
ABSTRACT Extensive grazing carried out freely by exotic goats represents an important source of anthropogenic degradation in seasonally dry tropical forests of Brazil. The presence of these herbivores may negatively impact the local fauna through the reduction of habitat complexity. In this study, we investigate the effect of goat farming in scorpion assemblage from Brazilian seasonally dry tropical forest. Scorpions were sampled in 36 areas (18 disturbed and 18 undisturbed) distributed in three sites in the seasonally dry tropical forest of Brazil. At each location, we recorded a set of local variables such as litter depth, diameter at breast height of trees, vegetation density (trees and shrubs), and detritus (stones and fallen logs). In total, 396 scorpions were collected, distributed across six species and two families. Our results showed that scorpion diversity was negatively affected, with species richness and abundance reduced in areas influenced by goats. Furthermore, in these sites, the composition of the species was also affected, with habitat‐generalist species favoring habitat‐specialist species. Finally, sites with free pasture of goats presented scorpions with reduced body condition (body mass and size) than sites without goats. Furthermore, habitat degradation caused by free pasture of goats negatively affects the assemblage of scorpions in terms of their diversity and body condition the seasonally dry tropical forest of Brazil.